2005
DOI: 10.1158/0008-5472.can-05-1317
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Cells Promote Osteoblastic Bone Metastases through Wnts

Abstract: Prostate cancer produces painful osteoblastic bone metastases. Although prostate cancer cells produce numerous osteogenic factors, to date, none have been shown to mediate osteoblastic bone metastases in an in vivo model of prostate cancer. Wnts are a large family of proteins that promote bone growth. Wnt activity is antagonized by endogenous proteins including dickkopf-1 (DKK-1). We explored if prostate cancer cells mediate osteoblastic activity through Wnts using DKK-1 as a tool to modify Wnt activity. A var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
250
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(273 citation statements)
references
References 25 publications
15
250
1
4
Order By: Relevance
“…Subsequent studies implicated DKK1 in the pathogenesis of osteolytic lesions in patients with multiple myeloma (Tian et al, 2003). During our study, Hall et al (2005) reported that PC-3 prostate cancer cells express DKK1 and showed by genetic manipulation of DKK1 in C4-2b prostate cancer cells that WNT signaling participates in prostate cancerinduced new bone formation. Our observations are consistent with these findings and extend further to the identification of the expression of WNT7b and DKK1 in human prostate cancer specimens.…”
Section: Discussionmentioning
confidence: 51%
“…Subsequent studies implicated DKK1 in the pathogenesis of osteolytic lesions in patients with multiple myeloma (Tian et al, 2003). During our study, Hall et al (2005) reported that PC-3 prostate cancer cells express DKK1 and showed by genetic manipulation of DKK1 in C4-2b prostate cancer cells that WNT signaling participates in prostate cancerinduced new bone formation. Our observations are consistent with these findings and extend further to the identification of the expression of WNT7b and DKK1 in human prostate cancer specimens.…”
Section: Discussionmentioning
confidence: 51%
“…In tumors with Wnt pathway defects, stabilized β-catenin interacts with TCF transcription factors to mediate increased expression of specific genes, at least some of which likely play critical roles in cancer pathogenesis (40). One of the well-known pathways that regulates oncogenesis in different organs is the Wnt signaling pathway (41). β-catenin is a downstream molecule in the Wnt signaling pathway and plays important roles in the structural organization and function of cell-to-cell adhesion and tumor invasion and metastasis (42).…”
Section: Discussionmentioning
confidence: 99%
“…In instances of osteolytic tumours, the presence of Dkk-1 would be predicted to exacerbate lesion formation through inhibition of Wnt-dependent osteogenesis. This certainly seems probable since a recent study has demonstrated that prostate tumours-expressing high levels of Dkk-1 produce more extensive local bone destruction compared to controls that express lower levels (Hall et al, 2005). Reducing the osteoinhibitory effects of Dkk-1 would therefore be predicted to reduce local bone damage, and as a result, probably reduce the expansion of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include multiple myeloma (Tian et al, 2003) and some forms of prostate cancer (Hall et al, 2005). Damage of the bone by malignancy can increase the severity of the disease by providing a permissive microenvironment for tumour growth and metastatic events.…”
mentioning
confidence: 99%